Therapeutic Achievements of a Program Based on Drama Therapy, the Theater of the Oppressed, and Psychodrama With Women Victims of Intimate Partner Violence - Mondolfi Miguel, Maria L. (Violence against women, 2021)
This case study aims to determine the efficacy of a program based on drama therapy, theater of the oppressed, and psychodrama to reduce psychological malaise (post-traumatic stress disorder [PTSD], depression, anxiety) and sexist stereotypes, and improve self-esteem, quality of life, life purpose, and communication skills in women victims of intimate partner violence. A pretest and a posttest were administered to a single group using psychometric instruments; in addition, an evaluation of the process was done using participatory observation. Findings show a statistically significant reduction of depression and increase in life purpose. Qualitative analyses suggest development of personal and social competencies and the elaboration of trauma.